The solutions of the perodic rational recursive systems - Uslu, Kemal; Kilic, E. (Communications in Mathematics and Applications, 2016)
In this study, we obtain the solutions of some perodic rational difference equation systems. Then we examinate the period of solutions of these systems.
Keywords: Periodic discrete system; Non-linear discrete system